Regulatory Chill and the Effect of Investor State Dispute Settlements - Eckhard Janeba (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2017)
Legal conflicts between multinational firms and host governments are often decided by international arbitration panels known as Investor State Dispute Settlements (ISDS). Critics fear that ISDS favors multinational firms, and make s governments reluctant to adopt appropriate policies (regulatory chill). I develop an economic model to analyze regulatory chill and show under which conditions a move to ISDS is beneficial.
Keywords: F23; F53; H25; 330